Deepfakes : the coming infocalypse - Schick, Nina, ....- (New York : Twelve, 2020)
"In a world of deepfakes, it will soon be impossible to tell what is real and what isn't. As advances in artificial intelligence, video creation, and online trolling continue, deepfakes pose not only a real threat to democracy -- they threaten to take voter manipulation to unprecedented new heights. This crisis of misinformation which we now face has since been dubbed the "Infocalypse." In DEEPFAKES, investigative journalist Nina Schick uses her expertise from working in the field to reveal shocking examples of deepfakery and explain the dangerous political consequences of the Infocalypse, both in terms of national security and what it means for public trust in politics. This all-too-timely book also unveils what this all means for us as individuals, how deepfakes will be used to intimidate and to silence, for revenge and fraud, and just how truly unprepared governments and tech companies are for what's coming."--Amazon.com.
Introduction: "fucked-up dystopia" -- R/Deepfakes -- Russia: the master -- The West: the internal threat -- The rest: global information disorder -- Deepfakes in the wild -- Covid-19: a global virus -- Allies, unite!
"Published in the UK as Deepfakes and the infocalypse by Monoray"--Title page verso.
Includes bibliographical references (pages 211-222).
Keywords: Disinformation; Information society; Political aspects